ANALISIS CAMPURAN BAHAN ALAM KULIT POHON BERINGIN TERHADAP KUAT TEKAN BETON (Menara: Jurnal Teknik Sipil, 2023)
Abstract Concrete is one of the main materials in a building or construction. In this study the results of a mixture of banyan tree bark on the concrete mixture produced the following compressive strength: a mixture with banyan tree bark 2% compressive strength value 18.66 MPa, 5% compressive strength value 17.17 MPa, 7% compressive strength value 12.33 MPa, 10% value compressive strength of 12.91 MPa and 13% 10.43 MPa. The increased water requirement in the concrete mixture using banyan tree bark makes the compressive strength of the concrete low. For a mixture of banyan tree bark 2% concrete bark added 200 grams of water that is planned, 5% shell concrete 400 grams of water added to meet the slump value, 7% shell concrete 1.6 kg of water added to meet the slump value, 10 % shell concrete 1.65 kg of water added to meet the slump value and 13% skin concrete 1.7 kg of water added to meet the slump value. As we know, concrete that absorbs a lot of water will affect the compressive strength of the concrete, so that concrete with high water absorption has a low compressive strength. Keywords: Concrete, banyan tree bark, compressive strength